Kamil Stefko (1875-1966) – profesor prawa i rektor Uniwersytetu Lwowskiego - Biłostockyj, Stepan (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
This article is devoted to the life of a famous Polish lawyer K. Stefko during his life in Lviv. The main stages of his professional career after finishing the study at the Lviv University: judge – lawyer – university lecturer are researched in the article. The stages of preparation for the candidate for the position of judge and lawyer in Lviv in the Austrian period are illustrated with the example of Prof. Stefko. His work as a judge of a district court in Brody is discussed. The article discusses his activity as the Dean of the Faculty of Law and the acting rector of Lviv University, mentioning his high reputation among the teachers of the faculty, his hard work, professionalism, high respect of rights, tolerance and patriotism. He was one of the few professors who supported the reform of academic education in 1933. The article also analyzes his legislative activity in the Codification Commission and presents an analysis of the scientific papers on civil procedure and international law, written in Lviv. Prof. Stefko paid great attention to the research of principles and sources of civil procedural law, the legal status of the participants and judges in civil proceedings, assessment of the evidence by the court, distance proceedings and the execution of court decisions. He indicated the influence of international law on national civil law. A characteristic feature of Prof. K. Stefko’s scientific works was the fact that they were based on the analysis of contemporary scientific theories of different civil schools and their practical implementation in the legislation of European countries.
Keywords: dean of the faculty; judge; lawyer; international civil disputes; Codification Commission; Austrian civil procedure; rector of the University; court civil proceeding; The Court of Competence; Lviv University; diplomatic immunity